Probabilitas Pemilihan Angkutan Umum Bus dan Kereta Api - Rizki, Reza Fauzabil; Farida, Ida (Universitas Kristen Maranatha, 2024)
The reactivation of Garut train station offers a transportation alternative for Garut Regency residents, with a focus on enhancing mobility and boosting tourism. While the railway station has been reactivated, several factors come into play when people choose between buses and trains for public transportation. This study involved a random sample of the entire population and employed quantitative research methods, including multiple linear regression, to analyze various variables. The characteristics of travelers in the study are primarily women aged 21-25, with a monthly income between Rp. 2,000,000 and Rp. 4,000,000, working in the private sector, holding high school diplomas, traveling less than five times, preferring buses, and considering travel time. Factors influencing the choice between buses and trains include cost (X1), travel time (X2), and mode availability (X4). Multiple linear regression results yielded the equation Y = -2.008 (a) + 0.266 (X1) + 0.158 (X2) + 0.378 (X3) + 0.405 (X4). This data was further utilized in a binary logit model to determine the probability values of alternative public transport choices, revealing a 72% probability of choosing the bus and a 28% probability of selecting the train.